Pharmacological and non-pharmacological interventions in patients undergoing nasal surgeries for prevention of emergence agitation: a systematic review and network meta-analysis - Gustavo R.M. Wegner; Bruno F.M. Wegner; Henrik G. Oliveira; Luis A. Costa; Luigi W. Spagnol; Valentine W. Spagnol; Gilberto T.F. de Oliveira Filho (Brazilian Journal of Anesthesiology)
Background: Emergence agitation is a common complication after nasal surgeries, marked by increased agitation and a heightened risk of injuries. Factors like urinary catheter, endotracheal tube, postoperative pain, and younger age contribute to its occurrence. Due to the variety of preventive approaches reported in the literature, a network meta-analysis is essential. Methods: This systematic review employs a network meta-analysis design, following Cochrane Handbook and PRISMA-NMA criteria. Inclusion criteria involve randomized controlled studies on pharmacological and non-pharmacological interventions for preventing emergence agitation in nasal surgeries. Electronic searches, including PubMed, Scopus, Embase, Cochrane Library, and Web of Science, without language or date restrictions, were conducted. Two independent reviewers selected studies, and data extraction was performed using standardized tables. Bayesian NMA, MetaInsight web app, and Cochrane Foundation Risk of Bias Assessment Tool were applied for data analysis and bias assessment. Results: After a rigorous selection process, 17 Randomized Controlled Trials (RCTs) encompassing 2,122 patients and 14 interventions were included. The best ranked treatments identified were intraoperative dexmedetomidine (1 μg.kg-1 for 10 minutes as a bolus, followed by 0.4 μg.kg-1.h-1), bilateral nasociliary and maxillary nerve block, ketamine (0.5 mg.kg-1 administered 20 minutes before the end of surgery), nasal compression for 40 minutes before anesthesia induction, and suction above the cuff of the endotracheal tube. Conclusions: Both pharmacological and non-pharmacological interventions emerged as effective strategies in mitigating emergence agitation after nasal surgeries, offering clinicians valuable options for improving postoperative outcomes in this patient population.